2021
DOI: 10.1186/s12891-021-04808-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various core decompression techniques versus non-operative treatment for osteonecrosis of the femoral head: a systemic review and network meta-analysis of randomized controlled trials

Abstract: Background Various Joint-preserving therapy (JPT) methods have been performed and tried in recent decades, but their results and efficacy were inconsistent and controversial. The purpose of this study is to evaluate its effectiveness and whether there are statistical differences in treatment between different interventions based on published RCT studies. Methods Following the PRISMA-NMA checklist, Medline, EMBASE, Web of Science, and Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…In a previous meta-analysis, Mont defined an HHS > 80 as clinical success and reported a higher clinical success rate in the surgical hip preservation group (64%) than in the nonsurgical treatment group (23%) ( 15 ). However, in a recent network meta-analysis, the HHS of the hip preservation surgery group was not significantly higher than that of the nonsurgical treatment group ( 17 ). Neumayr et al ( 24 ) used the modified HHS score and found that improvements in the scores did not significantly differ between the two groups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In a previous meta-analysis, Mont defined an HHS > 80 as clinical success and reported a higher clinical success rate in the surgical hip preservation group (64%) than in the nonsurgical treatment group (23%) ( 15 ). However, in a recent network meta-analysis, the HHS of the hip preservation surgery group was not significantly higher than that of the nonsurgical treatment group ( 17 ). Neumayr et al ( 24 ) used the modified HHS score and found that improvements in the scores did not significantly differ between the two groups.…”
Section: Discussionmentioning
confidence: 89%
“…Core decompression (CD) is the most common surgery for the treatment of ONFH prior to collapse, and the THA rate at 26 months after surgery is approximately 38% ( 35 37 ). Previous studies have shown that the THA rates do not significantly differ between nonsurgical and CD treatments ( 17 ). This finding was also observed in this study, and the THA rate with protective weight-bearing was approximately 40%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Till date, however, no statistically signi cant differences in the radiological progression of necrosis and the rate of conversion to arthroplasty, as well as PROM between surgical procedures regarding CD, have been reported 12,13,17,19,21,22 . Only cell therapy combined with CD has shown relatively superior outcomes regarding the radiological progression of ON 11,12,23−27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts have been made to improve the clinical outcomes by combining various procedures, such as vascularized or non-vascularized bone grafts, tantalum rods, and cell therapy with conventional CD [8][9][10] . In several randomized controlled trials (RCT) and meta-analyses, CD combined with cell therapy showed superior clinical outcomes in patients with early ONFH without head collapse [11][12][13] . Notably, the results of these procedures are still inconsistent among studies, and the evidence is too weak to build a general consensus for a treatment algorithm 14 .…”
Section: Introductionmentioning
confidence: 99%